Assaying the Potency of Influenza Vaccines - Philip D. Minor (Vaccines, 2015)
The potency of vaccines must be determined to ensure that the appropriate dose is given. The manufacture and assessment of influenza vaccines are complicated by the continuously changing nature of the pathogen, which makes efficacy estimates difficult but also confounds attempts to produce a well-validated, consistent potency assay. Single radial diffusion has been used for decades and provides a relatively simple way to measure the amount of biologically active materials present in the vaccine. It requires reagents, which are updated on a regular, frequently yearly, basis and alternative methods continue to be sought.